Atomic layer etching of silicon nitride using infrared annealing for short desorption time of ammonium fluorosilicate. (28th April 2017) - Miyoshi, Nobuya; Kobayashi, Hiroyuki; Shinoda, Kazunori; Kurihara, Masaru; Watanabe, Tomoyuki; Kouzuma, Yutaka; Yokogawa, Kenetsu; Sakai, Satoshi; Izawa, Masaru
Abstract: An atomic layer etching process for silicon nitride (Si3 N4 ) has been developed in which ammonium fluorosilicate [(NH4 )2 SiF6 ] is formed and desorbed using infrared annealing. The cycle of forming and removing ammonium fluorosilicate was repeated, demonstrating that the Si3 N4 etching depth was accurately controlled with high selectivity to SiO2 by changing the number of cycle. An X-ray photoelectron spectroscopy peak, which had been previously assigned as N–H bond of an ammonium salt, was observed after radical exposure, indicating that the ammonium fluorosilicate-based modified layer had formed. This peak disappeared after infrared annealing for 10 s, demonstrating desorption of the modified layer. In thermal desorption spectroscopy, NH3, HF, and SiF x were detected, providing further evidence for the formation of the ammonium fluorosilicate-based modified layer. In addition, this layer has a multilayer structure, protecting the Si3 N4 from exposure to reactive radicals.